The effect of folic acid on lipid peroxidation in women with polycystic ovary syndrome - H.Al-Mosawi, Reyadh; Hamood, Nuha J. (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: Polycystic ovary syndrome (PCOS) is one of the important causes of infertility Worldwide and affects about 20% of infertile couples. Women with PCOS have a surged risk of first trimester spontaneous abortion ranging from 25% to 73%. Oxidative stress has been linked to various disorders; including epilepsy, depression, ulcerative colitis and other diseases. However, it is still unknown whether it is a cause or a consequence in PCOS. Aim of the study: The aim of this study was to evaluate the effect of folic acid 5mg/daily on lipid peroxidation in adult females with polycystic ovary syndrome. Methods: The current study was carried out on 120 women in reproductive period, their ages ranged from 18 to 39 years. They were organized into three groups: group one studied 40 women having a PCOS treated with 5mg/day folic acid/day for 3 months, group two included 40 adult females without PCOS treated with 5mg/day folic acid/day for 3 months, And group 3 included 40 females with PCOS not treated with 5mg/day folic acid/day. Results: Folic acid administration at a daily dosage of 5 mg was found to reduce significantly the rate of lipid peroxidation byproduct, malondialdehyde (MDA) in PCOS women. Conclusion: It was clear that folic acid supplementation to PCOS women in a given pharmacological dose might have a positive effect on oxidative stress.